Location via proxy:   [ UP ]  
[Report a bug]   [Manage cookies]                

MAM1019H Notes

Download as pdf or txt
Download as pdf or txt
You are on page 1of 10

Chapter 2: Logic

2.1 Statements
A statement is a sentence or a mathematical expression that is either definitely true (𝑇 ), or definitely
false (𝐹 ).

Examples
• 1 + 1 = 2. Statement, 𝑇 .
• 1 + 1 = 3. Statement, 𝐹 .
• The fish. Not a statement.
• 1 + 1. Not a statement.
• UCT is in Cape Town. Statement, 𝑇 .
• Julius Malema is the leader of the DA. Statement, 𝐹 .
• The square of any real number is positive. Statement, 𝐹 (as 02 < 0).
• 𝑥2 = 4. Not a statement, as it depends on the value of 𝑥. It is an open sentence as it depends on the
value of one or more variables. Open sentences can be named, e.g 𝑃 (𝑥) : 𝑥2 = 4.
• If 𝑥 is an integer, then 𝑥 is even. Statement, 𝐹 . It is not an open sentence as the variable does not
change the truth value of the statement.
• 𝑝(𝑥) is a polynomial. Open sentence.
• If 𝑥2 = 4, then 𝑥 = 2. Statement, 𝐹 .
• 𝑥 + 𝑦 ≥ 0. Open sentence, as 𝑥 or 𝑦 could or could not be summed to be positive.
• If 𝑥, 𝑦 ∈ ℝ, then 𝑥 + 𝑦 ≥ 3. Statement, 𝐹 , as this is making a statement over all the reals.
• 𝑥 = 4. Open sentence, as 𝑥 could be something else.
• Let 𝑥 = 4. Neither a statement nor an open sentence - it is a command.
• Mathematical theorems are statements: Theorem: if 𝑓 is differentiable, then 𝑓 is continuous.
Statement, 𝑇 .
• Theorem: if 𝑎, 𝑏, and 𝑐 are the lengths of the sides of a right-angled triangle, with 𝑐 being the
hypotenuse, then 𝑎2 + 𝑏2 = 𝑐2 . Statement, 𝑇 .
• 𝑥 + 1 > 𝑥. Statement, 𝑇 , as this is true regardless of the value of 𝑥.

2.2 And, or, not


Examples
• 𝑃 : UCT is in Cape Town and 1 + 1 = 3. 𝐹
• 𝑄: UCT is in Cape Town and 1 + 1 = 2. 𝑇

𝑷 𝑸 𝑷 ∧𝑸

𝑇 𝑇 𝑇

𝑇 𝐹 𝐹

𝐹 𝑇 𝐹

𝐹 𝐹 𝐹
𝑷 𝑸 𝑷 ∨𝑸

𝑇 𝑇 𝑇

𝑇 𝐹 𝑇

𝐹 𝑇 𝑇

𝐹 𝐹 𝐹

𝑷 ¬𝑷

𝑇 𝐹

𝐹 𝑇

2.3 Conditional statements


Let 𝑃 , 𝑄 be statements or open sentences. We write:
𝑃 ⇒ 𝑄 (𝑃 implies 𝑄)

if whenever 𝑃 is 𝑇 , 𝑄 has to be 𝑇 as well.

Examples
• 𝑃 : I am a MAM1019H student
𝑄 : I am a UCT student
𝑃 ⇒ 𝑄 - if I am a MAM1019H student, then I am a UCT student.
?
𝑄 ⇒ 𝑃 - not always. This is known as the converse.
• 𝑥 = 2 ⇒ 𝑥2 = 4
But, 𝑥2 = 4 ⇏ 𝑥 = 2
• 6 ∣ 𝑥 ⇒ 3 ∣ 𝑥. True, as 3 ∣ 6.
But, 3 ∣ 𝑥 ⇏ 6 ∣ 𝑥, as 3 ∣ 3 but 6 ∤ 3
• 𝑥 = 4 ∧ 𝑦 = 3 ⇒ 𝑥 + 𝑦 = 7. True.
But, 𝑥 + 𝑦 = 7 ⇒ 𝑥 = 4 ∧ 𝑦 = 3.
• 2 ∣ 𝑛 ⇒ 3 ∣ 𝑛. False. Let 𝑛 = 4. Then, 2 ∣ 𝑛 but 3 ∤ 𝑛.

𝑷 𝑸 𝑷 ⇒𝑸

𝑇 𝑇 𝑇

𝑇 𝐹 𝐹

𝐹 𝑇 𝑇

𝐹 𝐹 𝐹

2.4 Biconditional statements


The converse of 𝑃 ⇒ 𝑄 is 𝑄 ⇒ 𝑃 .
Example:

𝑃 : I am a MAM1019H student
𝑄 : I am a UCT student
Then 𝑃 ⇒ 𝑄. However, 𝑄 ⇒ 𝑃 .

If (𝑃 ⇒ 𝑄) ∧ (𝑄 ⇒ 𝑃 ) then we say 𝑃 ⇔ 𝑄, or 𝑃 if and only if 𝑄.

Examples
• 𝑥 = 2 ⇒ 𝑥2 = 4
𝑥2 = 4 ⇏ 𝑥 = 2
• Claim: 𝑥2 ⇔ 𝑥 = 2 ∨ 𝑥 = −2
1. 𝑥2 = 4 ⇒ 𝑥 = 2 ∨ 𝑥 = −2
Suppose 𝑥2 = 4, then

𝑥2 − 4 = 0
(𝑥 − 2)(𝑥 + 2) = 0
𝑥 − 2 = 0 or 𝑥 + 2 = 0
2. 𝑥 = 2 ∨ 𝑥 = −2 ⇒ 𝑥2 = 4
1. 𝑥 = 2 : 22 = 4
2. 𝑥 = −2 : (−2)2 = 4

𝒙=𝟐 𝒙 = −𝟐 𝒙 = 𝟐 ∨ 𝒙 = −𝟐

𝑇 𝑇 (Left impossible)

𝑇 𝐹 𝑇

𝐹 𝑇 𝑇

𝐹 𝐹 𝐹

• Iff 𝑥 = 2 : 𝑥2 = 4.
• Iff 𝑥 = −2 : 𝑥2 = 4.
• Therefore, 𝑥 = 2 ∧ 𝑥 = −2 ⇔ 𝑥2 = 4
• 𝑥𝑦 = 0 ⇔ 𝑥 = 0 ∨ 𝑦 = 0
• Let 𝑥, 𝑦 ∈ 𝑅, then
𝑥𝑦 > 0 ⇔ (𝑥 > 0 ∧ 𝑦 > 0) ∨ (𝑥 < 0 ∧ 𝑦 < 0)
• Theorem from MAM1000W: if 𝑓 is differentiable, then 𝑓 is continuous.
However, the reverse does not hold: 𝑃 ⇎ 𝑄
• Let 𝑝(𝑥) be a polynomial over ℝ and 𝑎 ∈ ℝ
Then, 𝑝(𝑎) = 0 ⇔ (𝑥 − 𝑎) ∣ 𝑝(𝑥)
Example:
• 𝑝(𝑥) = 𝑥2 − 𝑥 − 2
𝑝(−1) = (−1)2 − (−1) − 2 = 1 + 1 − 2 = 0

∴ (𝑥 − 1) ∣ 𝑝(𝑥)
Definition
We define 𝑃 ⇔ 𝑄 as (𝑃 ⇒ 𝑄) ∧ (𝑄 ⇒ 𝑃 ):

𝑷 𝑸 𝑷 ⇒𝑸 𝑸⇒𝑷 (𝑷 ⇒ 𝑸) ∧ (𝑸 ⇒ 𝑷 )

𝑇 𝑇 𝑇 𝑇 𝑇

𝑇 𝐹 𝐹 𝑇 𝐹

𝐹 𝑇 𝑇 𝐹 𝐹

𝐹 𝐹 𝑇 𝑇 𝑇

Or,

𝑷 𝑸 𝑷 ⇔𝑸

𝑇 𝑇 𝑇

𝑇 𝐹 𝐹

𝐹 𝑇 𝐹

𝐹 𝐹 𝑇

Note that 𝑃 ⇔ 𝑄 if and only if 𝑃 = 𝑄, as can be seen from the truth table.

Setting up truth tables


This is how to do it to avoid losing marks:

𝑷 𝑸 𝑹

𝑇 𝑇 𝑇

𝑇 𝑇 𝐹

𝑇 𝐹 𝑇

𝑇 𝐹 𝐹

𝐹 𝑇 𝑇

𝐹 𝑇 𝐹

𝐹 𝐹 𝑇

𝐹 𝐹 𝐹
Essentially, this can be seen as counting down in binary from the top to the bottom row, if 𝑇 is taken
as 1 and 𝐹 as 0. E.g, 111 = 𝑇 𝑇 𝑇 .

The law of contrapositive


Prove that 𝑃 ⇒ 𝑄 = (¬𝑄 ⇒ ¬𝑃 ):

𝑷 𝑸 𝑷 ⇒𝑸 ¬𝑸 ¬𝑷 ¬𝑸 ⇒ ¬𝑷

𝑇 𝑇 𝑇 𝐹 𝐹 𝑇

𝑇 𝐹 𝐹 𝑇 𝐹 𝐹

𝐹 𝑇 𝑇 𝐹 𝑇 𝑇

𝐹 𝐹 𝑇 𝑇 𝑇 𝑇

As the columns for 𝑃 ⇒ 𝑄 and ¬𝑄 ⇒ ¬𝑃 are the same, we see that 𝑃 ⇒ 𝑄 = (¬𝑄 ⇒ ¬𝑃 ).
This can be used to execute proofs by the contrapositive.

De Morgan’s laws
• ¬(𝑃 ∧ 𝑄) = (¬𝑃 ) ∨ (¬𝑄)
• ¬(𝑃 ∨ 𝑄) = (¬𝑃 ) ∧ (¬𝑄)

Proof

𝑷 𝑸 𝑷 ∧𝑸 ¬(𝑷 ∧ 𝑸) ¬𝑷 ¬𝑸 (¬𝑷 ) ∨ (¬𝑸)

𝑇 𝑇 𝑇 𝐹 𝐹 𝐹 𝐹

𝑇 𝐹 𝐹 𝑇 𝐹 𝑇 𝑇

𝐹 𝑇 𝐹 𝑇 𝑇 𝐹 𝑇

𝐹 𝐹 𝐹 𝑇 𝑇 𝑇 𝑇

Chapter 1: Sets
1.1 Introduction
Sets can be written in many ways.
With patterns:
𝑆 = {2, 4, 6, 8, 10, 12}
= {2, 4, 6, …, 12}

Set of all 𝑥 for which the open sentence is 𝑇 :


𝑆 = {𝑥 : 𝑥 is even and 2 ≤ 𝑥 ≤ 12}
= {2𝑘 : 𝑘 ∈ 𝑅 ∧ 1 ≤ 𝑘 ≤ 6}

Set of all 𝑥 for which two open sentences are both 𝑇 :


𝑆 = {𝑥 ∈ 𝔼 : 2 ≤ 𝑥 ≤ 12}, where E is the set of even numbers

The cardinality of a set is the number of elements which it contains. It is written as |𝑆|.

Some common sets


ℕ = {1, 2, 3, 4, 5, …} — the natural numbers
ℕ+ = {1, 2, 3, 4, 5…} — the natural numbers explicitly from 1
ℕ0 = {0, 1, 2, 3, 4, 5, …} — the natural numbers including 0
ℤ{…, −3, −2, −1, 0, 1, 2, 3, …} — the integers
𝑚
ℚ = {𝑥 : 𝑥 = 𝑛
for some 𝑚, 𝑛 ∈ ℝ, 𝑛 ≠ 0}
𝑚
= {𝑥 : ∃𝑚, 𝑛 ∈ 𝑄 ∧ 𝑛 ≠ 0 ∧ 𝑥 = 𝑛
}

ℝ is the real numbers.


∅ is the empty set. ∅ = {}. |∅| = 0.

1.2 Cartesian products


If 𝐴, 𝐵 are sets, then the Cartesian product of 𝐴 and 𝐵 is 𝐴 × 𝐵 = {(𝑎, 𝑏) : 𝑎 ∈ 𝐴 ∧ 𝑏 ∈ 𝐵}

1.8 Indexed sets


Let 𝑎, 𝑏 ∈ 𝑅. We define 𝑎 ⊕ 𝑏 = 𝑎+𝑏2
. In other words, 𝑎 ⊕ 𝑏 is the average of 𝑎 and 𝑏. Notice that
(0 ⊕ 0) ⊕ 6 = 0 ⊕ 6 = 3, but also 0 ⊕ (0 ⊕ 6) = 0 ⊕ 3 = 32 . Therefore, ⊕ is a non-associative
operator. This means that 𝑎 ⊕ 𝑏 ⊕ 𝑐 is not well defined, as the order of operations is unclear.
Brackets will be required to disambiguate the order.
We can define ∪ and ∩ as follows for 3 sets, since they are associative operators:
𝐴1 ∪ 𝐴2 ∪ 𝐴3 = {𝑥 : 𝑥 ∈ 𝐴1 ∨ 𝑥 ∈ 𝐴2 ∨ 𝑥 ∈ 𝐴3 }
𝐴1 ∩ 𝐴2 ∩ 𝐴3 = {𝑥 : 𝑥 ∈ 𝐴1 ∧ 𝑥 ∈ 𝐴2 ∧ 𝑥 ∈ 𝐴3 }

However, we can also define this generally:


𝐴1 ∪ 𝐴2 ∪ … ∪ 𝐴𝑛 = {𝑥 : 𝑥 ∈ 𝐴1 ∨ 𝑥 ∈ 𝐴2 ∨ … ∨ 𝑥 ∈ 𝐴𝑛 }
= {𝑥 : ∃𝑖 ∈ {1, 2, 3, …, 𝑛}, 𝑥 ∈ 𝐴𝑖 }

𝐴1 ∩ 𝐴2 ∩ … ∩ 𝐴𝑛 = {𝑥 : 𝑥 ∈ 𝐴1 ∧ 𝑥 ∈ 𝐴2 ∧ … ∧ 𝑥 ∈ 𝐴𝑛 }
= {𝑥 : ∀𝑖 ∈ {1, 2, 3, …, 𝑛}, 𝑥 ∈ 𝐴𝑖 }

Example
For 𝑖 ∈ ℕ, let 𝐴𝑖 = [𝑖, 𝑖 + 1]

𝐴1 ∪ 𝐴2 ∪ 𝐴3 ∪ … = ⋃ 𝐴𝑖 = {𝑥 : ∃𝑖 ∈ ℕ, 𝑥 ∈ 𝐴𝑖 } = [𝑖, ∞)
𝑖=1


𝐴1 ∩ 𝐴2 ∩ 𝐴3 ∩ … = ⋂ 𝐴𝑖 = {𝑥 : ∀𝑖 ∈ ℕ, 𝑥 ∈ 𝐴𝑖 } = ∅
𝑖=1

Note that we can write


∞ ∞
⋃ 𝐴𝑖 = ⋃ 𝐴𝑖 and ⋂ 𝐴𝑖 = ⋂
𝑖=1 𝑖∈ℕ 𝑖=1 𝑖∈ℕ
With the second notation, we can also write ⋃𝑖∈𝑅 𝐴𝑖 . In these cases ℝ would be the index set.

Example
1 1 1 1
⋃ (1 − , 1 + ) = (0, 2) ∪ ( , 1 + ) ∪ … = (0, 2)
𝑖∈ℕ
𝑖 𝑖 2 2
1 1 1 1
⋂ (1 − , 1 + ) = (0, 2) ∩ ( , 1 + ) ∩ … = {1}
𝑖∈ℕ
𝑖 𝑖 2 2

Groups
A group is an ordered pair (𝐺, ·) where 𝐺 is a set and · is an operation defined over 𝐺.

Set ordering
An element 𝑠 ∈ 𝑆 is a smallest element of 𝑆 if ∀𝑥 ∈ 𝑆 : 𝑠 ≤ 𝑥.
Every nonempty subset of ℕ has a smallest element. This is not true for ℝ: (0, 1) has no smallest
element.
A set is called “well-ordered” if every non-empty subset has a smallest element. ℕ is well-ordered
(truth equivalent to principle of mathematical induction) and ℝ is not well-ordered.

Russell’s paradox
Let 𝐴 = {𝑋 : 𝑋 is a set ∧ 𝑋 ∉ 𝑋}. Is 𝐴 ∈ 𝐴? If 𝐴 ∈ 𝐴, then 𝐴 does not satisfy 𝑋 ∉ 𝑋. If 𝐴 ∉ 𝐴,
then it does satisfy 𝑋 ∈ 𝑋, so it should be in 𝐴.

Gödel’s incompleteness theorem

4 Direct proof
4.1 Theorems
A theorem is a mathemtical statement that has been proven to be true.
Proofs have to be based on other correctly proven theorems all the way down, otherwise they
cannot be true. Often, definitions will be relied on and are very important.

Definitions
The integer 𝑚 is even if ∃𝑘 ∈ ℕ : 𝑛 = 2𝑘.
The integer 𝑚 is odd if ∃𝑘 ∈ ℕ : 𝑛 = 2𝑘 + 1.
The integers 𝑚 and 𝑛 have the same parity if 𝑚 and 𝑛 are both even or 𝑚 and 𝑛 are both odd.
Let 𝑎, 𝑏 ∈ ℤ. Then 𝑎 | 𝑏 if ∃𝑐 ∈ ℤ : 𝑎𝑐 = 𝑏.
If 𝑎 | 𝑏, then 𝑎 is a divisor of 𝑏 and 𝑏 is a multiple of 𝑎.
A number 𝑛 is prime if it has exactly two positive divisors, 1 and 𝑛. If 𝑛 has more than two positive
divisors, then 𝑛 is composite.
Let 𝑎, 𝑏 ∈ ℤ. The greatest common divisor of 𝑎 and 𝑏, gcd(𝑎, 𝑏) is the largest integer that is a
divisor of both 𝑎 and 𝑏.
The least common multiple (lcm(𝑎, 𝑏)) is the smallest integer that is a multiple of 𝑎 and a multiple
of 𝑏.
4.2 Direct proof
Many mathematical theorems are in the form 𝑃 ⇒ 𝑄. To prove that this is true, we need to prove
the truth table of 𝑃 ⇒ 𝑄, but just for the case of 𝑃 being true.
Direct proof: prove that when 𝑃 is true, 𝑄 must be true. It begins by supposing 𝑃 and adding
logical steps until 𝑄 is shown to be true.

Example:
Prove that 𝑛2 is odd if 𝑛 is odd.
𝑛 is odd ⇒ ∃𝑘 ∈ ℤ, 𝑛 = 2𝑘 + 1
(2𝑘 + 1)2 = 4𝑘2 + 4𝑘 + 1
Let 𝑝 = 2𝑘2 + 2𝑘
𝑝 ∈ ℤ since the integers are closed under multiplication and addition
∴ (2𝑘 + 1)2 = 2𝑝 + 1

Example 2:
Prove that 𝑎|𝑏 ∧ 𝑏|𝑐 ⇒ 𝑎 | 𝑐.
Suppose 𝑎|𝑏 ∧ 𝑏|𝑐
𝑎|𝑏 ⇒ ∃𝑘1 ∈ ℤ, 𝑏 = 𝑘1 𝑎
𝑏|𝑐 ⇒ ∃𝑘2 ∈ ℤ, 𝑐 = 𝑘1 𝑏
𝑐 = 𝑘1 𝑘2 𝑎
∴𝑎|𝑐

Example 3:
Prove that if 𝑓 is differentiable at 𝑎 then 𝑓 is continuous at 𝑎

Example 4:
Prove 𝑚|𝑛 ∧ 𝑛|𝑚 ⇒ |𝑚| = |𝑛|
Suppose 𝑚|𝑛 ∧ 𝑛|𝑚
Since 𝑚|𝑛, ∃𝑘 ∈ ℤ, 𝑚𝑘 = 𝑛
Since 𝑛|𝑚, ∃𝑝 ∈ ℤ, 𝑛𝑝 = 𝑚
𝑚𝑘 = 𝑛 ⇔ 𝑛𝑝𝑘 = 𝑛 ⇔ 𝑝𝑘 = 1

Case: 𝑘 ≠ 0 :
1
𝑘≠0⇔𝑝=
𝑘
By assumption, 𝑝 ∈ ℤ ∧ 𝑘 ∈ ℤ, so 𝑘 ≠ 0 ⇔ 𝑝 ∈ {1, −1} ∧ 𝑘 ∈ {1, −1}
𝑘 ≠ 0 ⇔ 𝑚𝑘 = 𝑛 ⇔ |𝑚𝑘| = |𝑛| ⇔ 𝑚 = 𝑛

Case: 𝑘 = 0 :
𝑚𝑘 = 𝑛 ⇔ 𝑛 = 0
But, by assumption, 𝑛 | 𝑚 and zero does not divide anything, so there is a contradiction, and 𝑘 ≠ 0.
𝑛 ∈ ℤ ⇒ 𝑛2 + 𝑛 is even

Suppose 𝑛 ∈ ℤ

Case 𝑛 is even :
𝑛 is even ⇔ 2|𝑛
⇔ ∃𝑘 ∈ ℤ, 2𝑘 = 𝑛
⇔ 𝑛2 + 𝑛 = (2𝑘)2 + 2𝑘 = 2(2𝑘2 + 𝑘)
Let 𝑝 = 2𝑘2 + 𝑘. Since multiplication and addition are closed under ℤ, 𝑝 ∈ ℤ. So, 2𝑝 = 𝑛2 + 𝑛 ⇔ 2|𝑛2 + 𝑛

Case 𝑛 is odd :
𝑛 is odd ⇔ ∃𝑞 ∈ ℤ, 2𝑞 + 1 = 𝑛
⇔ 𝑛2 + 𝑛 = (2𝑞 + 1)2 + (2𝑞 + 1) = 2𝑞 2 + 4𝑞 + 1 + 2𝑞 + 1 = 2𝑞 2 + 6𝑞 + 2
Let 𝑟 = 𝑞 2 + 3𝑞 + 1. Since multiplication and addition are closed under ℤ, 𝑟 ∈ ℤ. So, 2𝑟 = 𝑛2 + 𝑛 ⇔ 2 | 𝑛2 + 𝑛.

5.2 Congruence of integers


Let 𝑎, 𝑏, 𝑛 ∈ ℕ, 𝑛 ∣ (𝑎 − 𝑏) ⇔ 𝑎 ≡ 𝑏(mod 𝑛).

5.3 Mathematical writing


1. Begin each sentence with a word (e.g “Let”, “Because”)
2. End each sentence with a period (even when ending with maths)
3. Separate mathematical symbols and expressions with words
4. Do not misuse symbols as words
5. Avoid using unnecessary symbols
6. Use the first person plural (we)
7. Use the active voice
8. Explain each new symbol (variable) introduced
9. Avoid ambiguity around “it” (what does “it” refer to?)
10. Use “Since, because, as, for, so, thus, hence, therefore, consequently”
11. Clarity is the gold standard

7.1 Proving 𝑃 ⇔ 𝑄
1. Prove 𝑃 ⇒ 𝑄
2. Prove 𝑄 ⇒ 𝑃
3. Conclude ((𝑃 ⇒ 𝑄) ∧ (𝑄 ⇒ 𝑃 )) ⇔ (𝑃 ⇔ 𝑄)

8.1 Proving 𝑎 ∈ 𝐴
Get 𝐴 in the form of {𝑥 : 𝑃 (𝑥)} and then show 𝑃 (𝑎) is true. For {𝑥 ∈ 𝑆 : 𝑃 (𝑥)} also prove 𝑥 ∈ 𝑆.

8.2 Proving 𝐴 ⊆ 𝐵
Direct
Suppose 𝑎 ∈ 𝐴, do some steps, and conclude 𝑎 ∈ 𝐵.

Contrapositive
Suppose 𝑎 ∉ 𝐵, do some steps, and conclude 𝑎 ∉ 𝐴 either.

8.3 Proving 𝐴 = 𝐵
1. Prove that 𝐴 ⊆ 𝐵
2. Prove that 𝐵 ⊆ 𝐴
3. Conclude that 𝐴 ⊆ 𝐵 ∧ 𝐵 ⊆ 𝐴 ⇔ 𝐴 = 𝐵

11.1 Relations
A relation 𝑅 on a set 𝐴 is a subset of 𝐴 × 𝐴 such that {(𝑎, 𝑏) ∈ 𝐴 × 𝐴 : 𝑎𝑅𝑏}.
(𝑎, 𝑏) ∈ 𝑅 ⇔ 𝑎𝑅𝑏 and (𝑎, 𝑏) ∉ 𝑅 ⇔ 𝑎𝑅𝑏

11.2 Properties of relations


A relation 𝑥𝑅𝑦 is an open sentence, so it is either true or false depending on 𝑥, 𝑅, and 𝑦. Hence,
they can be combined with boolean logic operators, like 𝑥𝑅𝑦 ⇒ 𝑦𝑅𝑥.
1. 𝑅 is reflexive if 𝑥𝑅𝑥 for every 𝑥 ∈ 𝐴 (e.g =, ≤, ∣ `)
2. 𝑅 is symmetric if 𝑥𝑅𝑦 ⇒ 𝑦𝑅𝑥 (e.g ≠, =)
3. 𝑅 is transitive if 𝑥𝑅𝑦 and 𝑦𝑅𝑧 then 𝑥𝑅𝑧 (e.g ≤, <, ≥, >, =).
In diagram form,
1. 𝑅 is reflexive if there is a loop at each point (𝑥 → 𝑥)
2. 𝑅 is symmetric if for every edge 𝑥 → 𝑦 there is an edge 𝑦 → 𝑥
3. 𝑅 is transitive if for edges 𝑥 → 𝑦 → 𝑧 there is also 𝑥 → 𝑧.

11.3 Equivalence relations


A relation 𝑅 is an equivalence relation if it is reflexive, symmetric, and transitive.
• Equality: =
• Same parity
• Same sign
• Same parity and sign
• ≡ mod(𝑛)
An equivalence class containing 𝑎 is the subset of 𝐴 consisting of all the elements that relate to 𝑎
under 𝑅. It is denoted as [𝑎] = {𝑥 ∈ 𝐴 : 𝑥𝑅𝑎}.
If 𝐹 = { 𝑚𝑛
: 𝑚, 𝑛 ∈ ℤ, 𝑛 ≠ 0} then 𝐹 is the set of all fractions. Pretend division is undefind so 24 is
. .
distinct from 12 . Then define = such that 𝑎𝑏 = 𝑑𝑐 ⇔ 𝑎𝑑 = 𝑏𝑐. Hence this represents all fractions that
are equal to eachother.

11.4 Equivalence classes and partitions


[𝑎] = [𝑏] ⇔ 𝑎𝑅𝑏:
Suppose [𝑎 = 𝑏]. Then, by the reflexive property of 𝑅, so
𝑎 ∈ {𝑥 ∈ 𝐴 : 𝑥𝑅𝑎} = [𝑎] = [𝑏] = {𝑥 ∈ 𝐴 : 𝑥𝑅𝑏}. But 𝑎 belonging to {𝑥 ∈ 𝐴 : 𝑥𝑅𝑏} means 𝑎𝑅𝑏.
Hence, [𝑎] = [𝑏] ⇒ 𝑎𝑅𝑏.
Conversely, suppose 𝑎𝑅𝑏. First we will show [𝑎] ⊆ [𝑏]. Suppose 𝑐 ∈ [𝑎]. Since
𝑐 ∈ [𝑎] = {𝑥 ∈ 𝐴 : 𝑥𝑅𝑎}, then 𝑐𝑅𝑎 and 𝑎𝑅𝑏, so 𝑐𝑅𝑏 because 𝑅 is transitive. But 𝑐𝑅𝑏 implies
𝑐 ∈ {𝑥 ∈ 𝐴 : 𝑥𝑅𝑏} = [𝑏]. Then, 𝑐 ∈ [𝑎] implies 𝑐 ∈ [𝑏] so [𝑎] ⊆ [𝑏].
Now we will show [𝑏] ⊆ [𝑎] Suppose 𝑐 ∈ [𝑏]. As 𝑐 ∈ [𝑏] = {𝑥 ∈ 𝐴 : 𝑥𝑅𝑏}, we get 𝑐𝑅𝑏. Since we
assume 𝑎𝑅𝑏, so 𝑏𝑅𝑎 since 𝑅 is symmetric. Now we have 𝑐𝑅𝑏 and 𝑏𝑅𝑎, so 𝑐𝑅𝑎 because 𝑅 is
transitive. Then, 𝑐 ∈ [𝑏] implies 𝑐 ∈ [𝑎] hence [𝑏] ⊆ [𝑎].
Hence, [𝑎] = [𝑏].
{[𝑎] : 𝑎 ∈ 𝐴} forms a partition of 𝐴.

11.5 Integers modulo 𝑛

You might also like